Feasibility of hybrid off pump artery bypass grafting and transaortic transcatheter aortic valve implantation: A case series. Issue 7 (12th July 2016) - Manoly, Imthiaz; Hasan, Ragheb; Brazier, Andrew; Farooq, Vasim; Thompson, Thomas; Karunaratne, Devinda; Naylor, Heather; Fraser, Douglas
Abstract : Introduction: Patients with complex coronary artery disease and severe aortic stenosis unsuitable for conventional cardiac surgery pose a significant treatment challenge. This is especially difficult for patients where percutaneous revascularization is technically very challenging and/or would not offer as complete revascularisation compared to surgical revascularisation. In addition, patients who are unsuitable for transfemoral transcatheter aortic valve implantation (TAVI) pose an additional technical challenge, particularly with dual antiplatelet therapy (DAPT) following percutaneous coronary intervention (PCI). As a potential solution we describe the first case series of hybrid off‐pump coronary artery bypass grafting (CABG) combined with transaortic TAVI. Methods and results: Over a ten‐month‐period, four patients underwent hybrid off‐pump CABG combined with transaortic TAVI. A full sternotomy allowed off‐pump arterial and vein graft anastomosis to significantly stenosed coronaries. The first three patients had severe aorto‐iliac disease precluding femoral access; the fourth patient was deemed unsuitable for PCI. Transaortic TAVI using Edwards Sapien 3 valves were performed without complication in all four patients. Conclusion: The hybrid off‐pump CABG and transaortic TAVI procedure allows for more complete coronary revascularization, negates the need for DAPT, and minimizes treatment delay of a TAVI procedure, particularly in patients unsuitable for transfemoral access. We propose this as an important treatment option for the heart team to consider. © 2016 Wiley Periodicals, Inc.